Thiefing a Chance : Factory Work, Illicit Labor, and Neoliberal Subjectivities in Trinidad - Prentice, Rebecca (Book collections on Project MUSE., 2015)
"When an IMF-backed program of liberalization opened Trinidad's borders to foreign ready-made apparel, global competition damaged the local industry and unraveled worker entitlements and expectations but also presented new economic opportunities for engaging the "global" market. This fascinating ethnography explores contemporary life in the Signature Fashions garment factory, where the workers attempt to exploit gaps in these new labor configurations through illicit and informal uses of the factory, a practice they colloquially refer to as "thiefing a chance." Drawing on fifteen months of fieldwork, author Rebecca Prentice combines a vivid picture of factory life, first-person accounts, and anthropological analysis to explore how economic restructuring has been negotiated, lived, and recounted by women working in the garment industry during Trinidad's transition to a neoliberal economy. Through careful social coordination, the workers "thief" by copying patterns, taking portions of fabric, teaching themselves how to operate machines, and wearing their work outside the factory. Even so, the workers describe their "thiefing" as a personal, individualistic enterprise rather than a form of collective resistance to workplace authority. By making and taking furtive opportunities, they embrace a vision of themselves as enterprising subjects while actively complying with the competitive demands of a neoliberal economic order. Prentice presents the factory not as a stable institution but instead as a material and social space in which the projects, plans, and desires of workers and their employers become aligned and misaligned, at some moments in deep harmony and at others in rancorous conflict. Arguing for the productive power of the informal and illicit, Thiefing a Chance contributes to anthropological debates about the very nature of neoliberal capitalism and will be of great interest to undergraduate students, graduate students, and faculty in anthropology, labor studies, Caribbean studies, and development studies"--The publisher.